Transport of micro/nano biochar in quartz sand modified by three different clay minerals. Issue 1 (1st January 2021) - Liu, Yiman; Sun, Huimin; Sun, Jiaxue; Meng, Xiangmin; Jiang, Yanji; Wang, Nong
ABSTRACT: Biochar has received continuous attention in recent years due to its high specific surface area, rich micropores, and many types of functional groups. In this study, the migration behavior of modified micro-nano biochar (MMNBC) in heterogeneous media under the influence of ionic strength and flow rate was studied by column experiments. The results showed that the mobility of MMNBC could be increased by increasing the flow rate and decreasing IS. The retention of MMNBC in quartz sand coated with clay minerals was higher than that of pure quartz sand, and the difference existed due to the surface properties. The main reason is that the clay mineral coating adds cations on the surface of quartz sand, which generates electrostatic interaction with MMNBC, which promote the adsorption of MMNBC on the medium. This study provides a theoretical basis for effectively controlling the groundwater environment problems caused by the migration of biochar.